2020
DOI: 10.1080/02705060.2020.1816228
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation in feeding ecology of age-0 lake whitefishCoregonus clupeaformisin Lake Huron

Abstract: Age-0 lake whitefish Coregonus clupeaformis stomachs from western Lake Huron were examined in 2018 to evaluate spatial variation in feeding ecology. Overall, age-0 lake whitefish had narrow diet niches and similar feeding strategies across sites in western Lake Huron, with all sizes of age-0 lake whitefish specializing on one prey at each site, with some other prey eaten occasionally by most individuals as fish grew at some sites. Although prey selectivity and the dominant prey types varied among sites, feedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Juvenile fish generally have a more diverse diet than larval fish (Nunn et al 2012). Larval Lake Whitefish appear largely dependent on copepods (Freeberg et al 1990;Hoyle et al 2011;Pothoven 2020;Pothoven and Olds 2020), whereas early juvenile fish had a more diverse diet in Lakes Michigan and Huron, which may reflect not only greater ability to use more prey types, but also increasing availability of prey other than copepods (Claramunt et al 2010a;Pothoven et al 2014;Pothoven and Olds 2020). Pothoven and Olds (2020) found that despite differences in prey importance and selection across sites in Lake Huron, feeding success generally did not differ among sites, suggesting that juvenile Lake Whitefish can adapt to a variety of prey conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Juvenile fish generally have a more diverse diet than larval fish (Nunn et al 2012). Larval Lake Whitefish appear largely dependent on copepods (Freeberg et al 1990;Hoyle et al 2011;Pothoven 2020;Pothoven and Olds 2020), whereas early juvenile fish had a more diverse diet in Lakes Michigan and Huron, which may reflect not only greater ability to use more prey types, but also increasing availability of prey other than copepods (Claramunt et al 2010a;Pothoven et al 2014;Pothoven and Olds 2020). Pothoven and Olds (2020) found that despite differences in prey importance and selection across sites in Lake Huron, feeding success generally did not differ among sites, suggesting that juvenile Lake Whitefish can adapt to a variety of prey conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, Lake Whitefish undergo multiple ontogenetic diet shifts during the late larval/early juvenile stage (Claramunt et al 2010a;Pothoven et al 2014) as well as a morphological shift in mouth position from terminal to subterminal when they reach a length of about 40 mm (Claramunt et al 2010a). A recent diet study in Lake Huron indicated that early juvenile Lake Whitefish may have broad flexibility in their diets, but this adaptability might not entirely buffer their feeding success across varying environmental conditions (Pothoven and Olds 2020). Another recent study at a single site in Lake Michigan indicated that feeding success increased with preferred prey abundance for larval Lake Whitefish, but the relationship was less consistent for early juvenile fish, suggesting that other biotic or abiotic factors may be important (Pothoven 2020).…”
mentioning
confidence: 99%